A Tunable Optofluidic Microlaser in a Photostable Conjugated Polymer. Issue 50 (11th October 2018) - Tang, Shui‐Jing; Liu, Zhihe; Qian, Yan‐Jun; Shi, Kebin; Sun, Yujie; Wu, Changfeng; Gong, Qihuang; Xiao, Yun‐Feng
Abstract: The optofluidic laser has become an important platform for biological sensing and medical diagnosis. To date, fluorescent dyes and proteins have been widely utilized as gain materials for biological analysis due to their good biocompatibility, but the limited photostability restricts their reliability and sensitivity. Here, an optofluidic microlaser with an ultralow threshold down to 7.8 µJ cm −2 in the ultrahigh‐ Q whispering‐gallery microcavity, which is filled with a biocompatible conjugated polymer, is demonstrated. This conjugated polymer exhibits a significant enhancement in the lasing stability compared with a typical laser dye (Nile red). In the experiment, after 20 min of illumination with the excitation intensity of 23.2 MW cm −2, the lasing intensity of the conjugated polymer experiences a decrease of less than 10%, while the lasing feature of Nile red completely disappears. Additionally, by mechanically stretching the resonator, the lasing frequency can be fine‐tuned with the range of about 2 nm, exceeding the free spectral range of the resonator. Abstract : Tunable optofluidic microlasers with an ultralow threshold down to 7.8 μJ cm −2 are demonstrated in an ultrahigh‐ Q whispering‐gallery microcavity filled with a biocompatible conjugated polymer. Compared with typical laser dyes, the conjugated polymer exhibits a significant enhancement in lasing stability. This low‐threshold laser with excellent photostability could find widespread use in aqueous environments for biological sensing and medical diagnosis.